(untitled) (Journal of the Bangladesh Agricultural University, 2013)
The study presents the issues of rural women in Sadar Upazila of Gazipur district considering their participation in micro credit programs for poverty alleviation. Data were collected from 75 BRAC women beneficiaries of four villages following random sampling techniques. On the basis of credit, the respondents have been classified into three categories. These are: i) A-small credit (up to Tk.4000) ii) B-Medium credit (Tk.4001-7000) and iii) C-Large credit (Tk.7001-10000). Average credits received by the respondents were Tk. 3250, Tk. 5875, and Tk. 8895 by small, medium, and large categories, respectively. The average annual income and savings of the respondents were Tk. 24245 and Tk. 1106, respectively. The repayment rate was 69.81 percent. Level of education, size of own land area, amount of income, savings and amount of loan received were found to be positive contribution to loan repayment performance. The study clearly hints that micro credit provides greater opportunity for rural poor women to improve their socioeconomic conditions. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14919 J. Bangladesh Agril. Univ. 10(2): 277-282, 2012